Mentoring : effects of relationship formality, gender composition, and organisational distance on level of assistance : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Moore, Carol Diane (Massey University, 2002)
The literature concerning the influences on career and psychosocial functions of mentoring are inconsistent concerning formality (formal vs. informal initiation of the mentoring relationship), inconsistent concerning gender composition of the dyad, non-existent concerning the effect of the mentor and protégé being in the same or different organisations, but consistent concerning the effect of supervisory status, namely that mentors who supervise their protégés provide more career assistance than non-supervisory mentors. In order to see if the level of career and/or psychosocial assistance was different depending on formality of the mentoring relationship, gender composition of the mentoring relationship, and organisational distance between the mentor and protégé, a 198-item questionnaire was sent to 954 senior and executive New Zealand business people. Twenty seven percent returned questionnaires reporting on developmental relationships either as a mentor, a protégé, or other relationships. No female mentors with male protégés were analysed because of their paucity. In the analysis of data from 115 mentors it was found that career assistance was rated as more important than psychosocial assistance in determining impact on a protégé's career. It was found that the overall level of career assistance was affected by (a) the gender composition of the mentoring relationship and (b) whether the mentor was in the same organisation as the protégé. The overall level of psychosocial assistance was affected by (a) the gender composition of the mentoring relationship. The level of career and psychosocial assistance was not affected by (a) whether the mentor was a protégé's supervisor or not, or (b) whether the relationship was formal or informal in its initiation. Results suggest that (a) both male and female protégés should select (b) male mentors from (c) the same organisation for maximal (d) career and (e) psychosocial assistance. That nine covariates were used can account for the discrepancy in results with previous studies. A hypothesis for Protégé Influence is formulated and found to be superior to previous hypotheses of Mentor Power and Mentor Risk in accounting for differences in career-and psychosocial-assistance behaviour of mentors.
Keywords: Mentoring in business